Spectrum of Enteric Parasitic Infections in Immunocompromised and Immunocompetent Patients in a Tertiary Care Hospital, New Delhi- A Retrospective Study - Anuja Gupta; Monika Matlani; Vinita Dogra (National Journal of Laboratory Medicine, 2023)
Introduction: Parasitic intestinal diseases caused by protozoans and helminths are important causes of gastrointestinal disturbances which are responsible for a high burden of morbidity and mortality as they are detrimental not only to paediatric and immunocompromised patients but also to adults and immunocompetent patients. Hence, it is important to know their burden in a geographical area to develop adequate control measures. Aim: To estimate the prevalence of various intestinal parasitic infections in symptomatic patients based on age, gender and immune status in a tertiary care hospital, New Delhi, India. Materials and Methods: A retrospective analysis of 1431 stool samples which were received in the Department of Microbiology VMMC and Safdarjung Hospital, New Delhi, from April 2019 to March 2020 was done. All samples were subjected to macroscopic and microscopic examinations and underwent, wet mount (saline and iodine) examination and Modified Ziehl-Neelson staining. Data was analysed using Statistical Package for Social Sciences (SPSS) software version 21.0 with two-tailed Chi-square test wherever applicable. Results: Males (61.36%) outnumbered females. Prevalence of parasites was more in adults (7.76%) than in children. Higher positivity (7.6%) was observed in immunocompetent individuals as compared to immunocompromised. Overall predominance of protozoans (98.26%) over helminths was noted. Entamoeba histolytica/dispar group (43.60%) was found to be the most prevalent parasite. Entamoeba histolytica/dispar group (5.64%) and Cryptosporidium spp. (5.94%) were most common amongst immunocompetent and immunocompromised patients respectively. Conclusion: A higher prevalence of intestinal parasitic infections in immunocompetent symptomatic patients was observed, requiring attention of clinicians as they are no longer limited majorly to immunocompromised patients. As no effective vaccine is available for these infections, so appropriate laboratory methods, microbiological expertise, proper sanitation measures, availability of potable water supply and properly cooked food are essential to control parasitic intestinal diseases.